Collecting and analyzing network-based evidence - Ashwini K. Singh; Dhwaniket Kamble; Abhishek Bains; Naman Tiwari; Tejas R. Deshmukh; Sanidhya Pandey; Hemant Kumar; Diksha M. Bhalerao (Computer Science and Information Technologies, 2024)
Since nearly the beginning of the Internet, malware has been a significant deterrent to productivity for end users, both personal and business related. Due to the pervasiveness of digital technologies in all aspects of human lives, it is increasingly unlikely that a digital device is involved as goal, medium or simply ‘witness’ of a criminal event. Forensic investigations include collection, recovery, analysis, and presentation of information stored on network devices and related to network crimes. These activities often involve wide range of analysis tools and application of different methods. This work presents methods that helps digital investigators to correlate and present information acquired from forensic data, with the aim to get a more valuable reconstructions of events or action to reach case conclusions. Main aim of network forensic is to gather evidence. Additionally, the evidence obtained during the investigation must be produced through a rigorous investigation procedure in a legal context.